The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1590/s1806-83242008000100014
|View full text |Cite
|
Sign up to set email alerts
|

Image quality in partially erased DenOptix® storage phosphor plates

Abstract: This study aimed at investigating the effect of the partial erasing of DenOptix system storage phosphor plates on the image quality of digital radiographs. Standardized digital radiographs were acquired of a phantom mandible, using size 2 intraoral DenOptix storage phosphor plates (n = 10). Subsequently, the active areas of the plates were placed in a viewing box with a constant light intensity of 1,700 lux for 130 seconds to achieve complete erasing (control plate), as well as for 0,5,10,15, 20, 25, 34, 66, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…The results in this study differ from Lopes et al, 21 probably because in their study the observers were told to choose one of the paired images based on no specific criteria. Also, the object was an acrylic phantom fixed on the positioning apparatus to acquire a geometric pattern.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…The results in this study differ from Lopes et al, 21 probably because in their study the observers were told to choose one of the paired images based on no specific criteria. Also, the object was an acrylic phantom fixed on the positioning apparatus to acquire a geometric pattern.…”
Section: Discussioncontrasting
confidence: 94%
“…The presence of image noise on partially erased phosphor plates should be considered when enhancement of the image is needed. Versteeg et al 21 noted that digital image density can be increased until it is adequate for diagnosis, but the enhanced digital image will show an increase in noise. Therefore, a higher amount of noise may be generated during digital enhancement if the digital image already has increased noise due to a suboptimal erasing time which will interfere with the final image quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would reduce the number of procedures performed based on false-positive diagnoses, therefore reducing service costs. Thus, the relatively higher cost of the digital systems in comparison with conventional radiography18 can be expected to be made up for by the cost-effectiveness of the digital system.…”
Section: Discussionmentioning
confidence: 99%
“…12,18,19 After evaluating the effect of different erasing times on proximal caries diagnosis, Melo et al 12 reported no significant difference in both pixel intensity values and diagnostic accuracy of observers. Since the effect of various erasing times was tested, the methods of the former and the presented study were basically not the same; therefore, the comparison of the results may not be relevant.…”
Section: Discussionmentioning
confidence: 99%